Does active participation in health enhance health outcomes and healthcare delivery systems? - Thutloa, Alfred; Stroud, Christopher (Stellenbosch Papers in Linguistics Plus, 2013)
In 2000 a Committee of the United Nations Economic and Social Council recognised health as essential for exercising all other rights (Djité 2008). The World Health Organization (1998) also sees health as a vital resource for enabling citizens to lead individually, socially and economically productive lives. However health is one space where the opportunities to participate and exercise voice is directed by the provision of health resources and material. Now in late modernity health has become a goal for citizens to work towards or they risk suffering from chronic illness and premature death (Cockerham 2005). The procurement of health has also shifted from the state as the provider of equitable health care to all citizens to a commodity that can be purchased in an expanding health market place (Kickbusch 2004). If health has become the responsibility of the citizen, issues of health literacy, multimodal access to information and multilingualism need to be considered. This research report focuses on work produced as part of the first author’s doctoral project, exploring the phenomenon of consumption of health resources for health citizenship in the private health insurance industry. Based on data collected from 75 participants through an electronic questionnaire, as well as different genres of information utilised for health promotion, the project investigated how the construction of information and the multimodal tools used by two leading South African health insurers influenced the consumers’ health subjectivity. Data collected showed the importance of multilingual information, health literacy and multimodal tools for enabling participation and voice among consumers. In addition, the consumers proposed more accessible information and better designed newsletters and web sites to help them with information seeking for health knowledge and health citizenship.